2011
DOI: 10.1016/j.medengphy.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of forces and torque in conventional and ultrasonically-assisted drilling of cortical bone

Abstract: Citation: ALAM, K., MITROFANOV, A.V. and SILBERSCHMIDT, V.V., 2010.Experimental investigations of forces and torque in conventional and AbstractBone drilling is widely used in orthopaedics and surgery; it is a technically demanding surgical procedure. Recent technological improvements in this area are focused on efforts to reduce forces in bone drilling. This study focuses on forces and a torque required for conventional and ultrasonically-assisted tool penetration into fresh bovine cortical bone.Drilling tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
147
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(173 citation statements)
references
References 23 publications
(22 reference statements)
23
147
3
Order By: Relevance
“…The presented force and torque results overlap with some reports (Alam et al 2011, Lee et al 2012 which have values up to 70N and 3.8Ncm respectively. To the authors' knowledge, no 3D numerical study has been reported previously on the prediction of drilling force in cortical bone, only a few studies predict forces in plane cutting of cortical bone using FE models ( Alam et al 2009, Childs et al 2011.…”
Section: 5supporting
confidence: 72%
See 1 more Smart Citation
“…The presented force and torque results overlap with some reports (Alam et al 2011, Lee et al 2012 which have values up to 70N and 3.8Ncm respectively. To the authors' knowledge, no 3D numerical study has been reported previously on the prediction of drilling force in cortical bone, only a few studies predict forces in plane cutting of cortical bone using FE models ( Alam et al 2009, Childs et al 2011.…”
Section: 5supporting
confidence: 72%
“…Comparison to previous studies Current findings for maximum thrust force and torque are compared to those reported by others as shown in table 4 ( Wiggins et al 1976, Natali et al 1996, Ong et al 1999, Hillery et al 1999, Tsai et al 2007, Alam et al 2011, Lee et al 2012, MacAvelia et al 2012. The presented force and torque results overlap with some reports (Alam et al 2011, Lee et al 2012 which have values up to 70N and 3.8Ncm respectively.…”
Section: 5supporting
confidence: 54%
“…The drilling speed and feed rate were changed from 1000 rpm to 3000 rpm and 30 mm/min to 70 mm/min, respectively. These parameters were chosen since they were widely reported in the literature on drilling of bone [13,18,19]. Some research studies used the drilling speed up to 10000 rpm or above in bone-drilling experiments [3,20] but this did not become a common practice.…”
Section: Methodsmentioning
confidence: 99%
“…It is interesting to point out that in a previous study with ultrasonically-assisted drilling of cortical bone the thrust force was reduced from 60-65 N to 35-38 N by adding vibration ("back movement") during every drill turn. [12] In the current work the algorithm for force control is with similar features, however, without implementation of "back movement". In case the thrust force increases above an identified level, the linear drive of the robot stops until the force, monitored by its sensor, drops down to this level because of the zero linear speed and the continuing drill rotation in the bone.…”
Section: Drilling Without Overheatingmentioning
confidence: 99%
“…[6][7][8][9][10][11] Adding vibration during ultrasonically-assisted drilling of cortical bone was reported to reduce to some extent the resistant axial force. [12] However, such drilling is still manually performed with vibrations at constant frequencies and amplitudes without any further control.…”
Section: Introductionmentioning
confidence: 99%